Pengaruh Kesadaran Politik terhadap Partisipasi Politik pada Pemilihan Kepala Kampung Bakung Udik Kabupaten Tulang Bawang - Willya Apriyani; Muhammad Mona Adha; Edi Siswanto (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2024)
The aim of this research is to analyze the influence of political awareness on political participation in Bakung Udik Village, Tulang Bawang Regency. The method that used here is descriptive with a quantitative approach, involving 93 respondents. Data was analyzed using a simple linear regression test with the help of SPSS version 25. The results of the research show that respondents political awareness is divided into three indicators, namely output, input, and receipt of political information and freedom in giving opinions. 45.1% of respondents showed strong political awareness in output indicators, such as interest in political developments and participation in community organization. Input indicators, 46.2% of respondents have good political awareness, including knowledge of government policies and they understand that the government influences their lives. Indicators receiving political information and feeling the freedom to give opinions show that 69.8% are categorized as influential, indicating that they are well informed and have the freedom to give their opinions. Regression analysis shows that political awareness has a significant influence on political participation, with a coefficient of determination (Rsquare) is 44.6%. This means that 44.6% of the variation in political participation can be explained by the level of political awareness, while the remaining 55.4% is affected by other factors. Overall, the political participation of the people in Bakung Udik Village is already good, it looks from a fairly high percentage of the people participation compared to those who did not participate. The conclusion is, political awareness has an important influence for increasing political participation in village head elections.